Scientometric Analysis on Gender in Fisheries and Aquaculture: Global and Indian Trends: Scientometric Analysis on Gender in Fisheries and Aquaculture - Regu, Atufa; Ananthan, P. S.; Gopal, Nikita; Venkat, Suvetha; Argade, Shivaji Dadabhau (Fishery Technology, 2025)
A scientometric study on usage of gender neutral terms along with trends and patterns followed in literature corresponding to fisheries and aquaculture research, was undertaken, using Web of Science as a tool. It was found that a relatively high percentage (51.03% and 49.09%) of documents mentioned ‘fishers’ and ‘fishermen’ respectively. In contrast, in global literatures, individual and multiple mentions were less common for fisherwomen (1.8%) and fisherfolk (2.1%) between 2015 and 2021. In the Indian scenario, from 1990 to 2021, a relatively high percentage (59.6%) of documents that mentioned ‘fishermen’ also mentioned one of the other terms above, as individual and multiple mentions were less common for ‘fishers’ (36.6%), ‘fisherfolk’ (12%), and fisherwomen (7%). Also, the examination of equivalent terms for 'fishers,' 'fisherman,' and 'fisherwoman' revealed patriarchal notions in linguistic differences in how fishers are represented across Indian languages, reflecting deep-rooted societal biases and cultural diversity. Globally, the USA was found to be the main contributor in quantifiable terms (26.7%). Among journals, ‘Maritime Studies’ has the highest record count for publications (5%), whereas total citations (554) and average citation per paper (55.4) were found to be highest for the ‘Fish and Fisheries’ journal. In this regard, quantifying gender research can be a support and addendum to the present pool of literature and knowledge available in the field of gender in fisheries and aquaculture studies.